Analyzing the effects of macroeconomic and variables on systemic risk in the Philippine banking sector: An application of srisk model - Mercado, Lucila Pilar T. (Animo Repository, 2019)
This paper measures the systemic risk in the Philippine banking sector and analyzes the effect of macroeconomic and bank-specific factors on systemic importance. The study covered ten listed domestic banks {9 universal banks and 1 thrift bank) in the Philippine Stock Exchange, with data for the period 2007 to 2017. Analysis of data gathered will be conducted in two steps. First, systemic risk of the Philippine banking sector will be measured using the SRISK model as proposed by Brownlees and Engle {2016). Second, bank specific and macroeconomic factors and its impact to systemic risk will be analyzed using the multiple regression. The empirical evidence of this study revealed that the significant bank-specific factors influencing systemic risk are the size, capital adequacy ratio, leverage, non-performing loans ratio, and loans to deposit ratio. Results also showed that the main macroeconomic variables affecting systemic risk are gross domestic product growth rate and interest rate. The findings of this study will redound to the benefit of policymakers/regulators considering the significant role of banks in the financial system and increasing interconnectedness across financial institutions, while it is the primary mandate of the Bangko Sentral ng Pilipinas to promote and maintain financial stability. With the evolving faces of financial crisis, there is a greater need for tools that would effectively measure systemic risk. Hence, the researchers as well as the academic teachers may use the output of this research to establish data in order to explore and recalibrate, if necessary, other systemic risk monitoring tools that fits the Philippine banking sector.